Static allometry of a small-bodied omnivore: body size and limb scaling of an island fox and inferences for Homo floresiensis. Issue 149 (December 2020) - Young, Colleen B.
Abstract: Island dwarfing is a paraphyletic adaptation across numerous mammalian genera. From mammoths to foxes, extreme body size reduction is shared by diverse organisms that migrate to an island environment. Because it largely occurs owing to ecological variables, not phylogenetic ones, skeletal characters in a dwarfed taxon compared with its ancestor may appear abnormal. As a result, allometric patterns between body size and morphological traits may differ for an island dwarf compared with its ancestor. The diminutive Late Pleistocene hominin, Homo floresiensis, displays a unique character suite that is outside of the normal range of variation for any extinct or extant hominin species. To better explain these as ecological traits due to island dwarfing, this research looks at how dwarfing on islands influences limb scaling and proportions in an organism in a similar ecological niche as H. floresiensis . Here, I analyze absolute limb lengths and static allometry of limb lengths regressed on predicted body mass of dwarfed island foxes and their nondwarfed relatives. Dwarfed island foxes have significantly smaller intercepts but steeper slopes of all limb elements regressed on predicted body mass than the mainland gray fox. These allometric alterations produce limbs in the island fox that are significantly shorter than predicted for a nondwarfed gray fox of similar body mass. In addition, the humerofemoral, intermembral, and brachial indices are significantly different. These results provide a novel model for understanding skeletal variation of island endemic forms. Unique body size and proportions of H. floresiensis are plausible as ecological adaptations and likely not examples of symplesiomorphies with Australopithecus sp. Caution should be exerted when comparing an island dwarf with a closely related species as deviations from allometric expectations may be common. Highlights: Dwarfism in the island fox corresponds with novel community-resource dynamics. The small-bodied island fox is not a scaled-down version of the mainland fox. Body size reduction in an island omnivore produces unique body proportions. Body size and proportions of Homo floresiensis are likely ecological adaptations.